Bridging the divide between technologists and policy-makers. - Peha, J.M (IEEE spectrum)
Modern governments face an increasing number of issues that require extensive knowledge of science or technology for effective decision-making. These include issues of health care, environment, energy, agriculture, national defense, communications and transportation, to name a few. There is no shortage of expertise to address these issues; the majority of scientists and engineers who have ever lived are alive today. Yet all too often, the policy-making process does not benefit from this technical expertise. There is a great divide between technologists-research-oriented, forward-looking engineers and scientists-and policy-makers, elected legislators and their staffs at the local, state and Federal levels. As a result, we have a system in which policy-makers are too often deprived of knowledge that they need to do their job well, and in which technologists with this knowledge have limited influence. Each side may blame the other for its inaccessibility. At the core of this failure to communicate are two groups with different operational systems and different cultures